Intraoperative Catastrophes during Robotic Lung Resection: A Single-Center Experience and Review of the Literature - Beatrice Manfredini; Carmelina Cristina Zirafa; Gaetano Romano; Elena Bagalà; Claudia Cariello; Federico Davini; Franca Melfi (Life, 2023)
Background: Robotic surgery is increasingly used in the treatment of lung disease. Intraoperative catastrophes, despite their low incidence, are currently a critical aspect of this approach. This study aims to identify the incidence and management of catastrophic events in patients who underwent robotic anatomical pulmonary resection; (2) Methods: Data from all patients who underwent robotic anatomical pulmonary resection from 2014 to 2021 for lung disease were collected and analyzed. Catastrophic intraoperative events are defined as events that demanded emergency management for life-threatening bleeding, with or without undocking and thoracotomy; (3) Results: Catastrophic events occurred in seven (1.4%) procedures; all of them consisted of vascular damage during lobectomy. Most of the catastrophic events occurred during left upper lobectomies (57%). Patients in this group had a higher ASA class and a higher pathological stage compared to the control group; (4) Conclusions: Intraoperative catastrophes are unpredictable events which also occur in experienced surgical teams. Given the widespread use of robotic surgery, it is essential to develop well-defined crisis management strategies to better manage catastrophic events in robotic thoracic surgery and improve clinical outcomes.